The Role of the Private Sector in Reproductive Health Services in Bangladesh - Bennouna, Cyril (World Bank, Washington, DC, 2018)
The brief provides an overview of the most relevant programs promoting social accountability in Indonesia's primary health sector, with a focus on maternal and child health, and summarizes global and regional key lessons learned to inform future social accountability initiatives in the country. There are a number of programs in Indonesia that have increased citizens' access to information in the health sector and have empowered citizens to hold government accountable to basic health services. Some lessons include using multi-tool and multi-stakeholder approaches to social accountability strategies in order to reduce implementation risks in different contexts. Social accountability can reinforce programmatic gains by strengthening institutional mechanisms for problem solving.